Acceptability of a patient decision aid for women aged 70 and older with stage I, estrogen receptor-positive, HER2-negative breast cancer. Issue 5 (June 2021) - Minami, Christina A.; Freedman, Rachel A.; Karamourtopoulos, Maria; Pinheiro, Adlin; Gilliam, Elizabeth; Aliberti, Gianna; Pories, Susan E.; Recht, Abram; Lotz, Margaret; Dominici, Laura S.; Schonberg, Mara A.
Abstract: Objectives: A comprehensive decision aid (DA) for women ≥70 years with Stage I ER+/HER2-negative breast cancer was developed to support locoregional and systemic treatment decision-making. We aimed to test the acceptability of this novel DA in women newly-diagnosed with breast cancer. Materials and Methods: Women ≥70 diagnosed with Stage I, ER+/HER2- breast cancer were recruited from three Boston-area hospitals. They underwent baseline interviews after initial surgical consultation, reviewed the DA, and were surveyed <2 weeks later to determine DA acceptability (e.g., was it helpful?), changes in decisional conflict, stage of decision-making, and knowledge. Participants could optionally complete a three-month follow-up. Paired t -tests and McNemar's tests were used for statistical comparisons, and thematic analyses were conducted to identify themes in participants' open-ended comments. Results: Thirty-three of 56 eligible patients approached completed the baseline and acceptability surveys, and 25 completed the three-month follow-up. Participants' mean age was 74.7 years (±3.8). Nearly all participants ( n  = 31, 94%) strongly agreed that the DA was helpful and felt that the DA prepared them for treatment decision-making, with a mean decision preparation score of 4.1 (out of 5.0); 6% ( n  = 2) found it very anxiety provoking. Knowledge improved with a mean of 9.0 out of 14 questions correct at baseline to 10.6 correct on the acceptability survey ( p  < 0.0001). Conclusions: A DA tailored to women ≥70 with Stage I, ER+, HER2- breast cancer increased knowledge and was perceived to be helpful by older women. A randomized controlled trial is needed to evaluate its efficacy.